Avaliação do perfil imune em pacientes com linfoma de Hodgkin clássico com doença avançada - Icibaci, Priscilla Brito da Silva [UNIFESP] (2018)
Classic Hodgkin's lymphoma is a curable disease in most cases; however, approximately 25% of the patients present refractory or relapsed disease with a high rate of lethality. The tumor microenvironment consists of only 1 to 5% of neoplastic cells, named ReedSternberg (RS) cells; the remaining be composed of normal inflammatory cells. The reason for the lack of an effective immune response against the tumor remains unknown. Immune imbalance reflects not only the tumor microenvironment but also the particular anergic state of the patient with classical Hodgkin's lymphoma (cHL). Therefore, a better understanding of this complex network of cellular interactions involved in the immune response may contribute to the development of new biomarkers and potential therapeutic targets. Purpose: In this study, we aimed to evaluate immune gene expression profile by messenger RNAs in peripheral blood of patients with cHL. Correlate the presence of EpsteinBarr virus in RS cells with the expression of messenger RNAs in peripheral blood. Correlate the messenger RNAs expression with clinical and laboratory characteristics. To evaluate the impact of treatment on gene expression of messenger RNAs related to the immune profile. Correlate the messenger RNAs expression in peripheral blood of cHL patients with canonical pathways and gene networks. Validate immune gene expression profile by measure soluble proteins serum levels of cHL patients. Methods: We prospectively studied 27 cases of cHL diagnosed between October 2011 to October 2015 at the Universidade Federal de São Paulo and Hospital Santa Marcelina. Additionally, 10 healthy controls were included and recruited from our University Blood Bank. Peripheral blood samples of cHL patients were collected at diagnosis and after treatment. The general expression of 96 messengers RNAs present in the peripheral blood and involved in immune response was performed by a customized quantitative realtime PCR array (TaqMan®Low Density Array). The data was normalized with B2M mRNAs levels and relative gene expression was calculated by the 2^DDCt method, considering Wilcoxon test and BenjaminiHochberg adjustment to correct pvalues. Soluble proteins were measured by enzymelinked immunosorbent assay (ELISA). Results: Nineteen patients with cHL were evaluated, median age at diagnosis was 29 years, and 63% were male. IL23A expression were associated with the presence of EBV (p=0.040, p=0.054, p=0.040, respectively). We observed an increase in expression of CD274 (PDL1) (2 times p= 0.011), CD28 (1.5 times p= 0.049), CTLA4 (1.6 times p = 0.005), FAS (1.5 times – p=0.025), ICOS (2.3 times – p=0.004), IL10 (3 times p=0.003) and CASP1 (1.5 times – p=0,042) in the samples at diagnosis when compared to the end of treatment. Compared to healthy controls, we found higher expression of IL10 (2.5 times padj= 0.009) in the samples at diagnosis. Regarding the dosage of soluble proteins, we observed that patients with B symptoms (p=0.048), bulky disease (p=0.023), advanced staging (p=0.048), ESR and albumin altered (p=0.006, p=0.008 respectively) were associated with elevated levels of sPDL1, that had impact in overall survival of cHL patients. Increased levels of sCTLA4 were associated with highrisk IPS (p=0.013). Elevated levels of sPDL1 were observed at diagnosis when compared to healthy controls (p=0.023). After treatment the levels of IL10 (p=0.001), sPD1 (p = 0.006) and sPDL1 (p=0.002) were significantly reduced. Compared to healthy controls IL10 levels remained high (p=0.0003). Conclusion: This study demonstrates an increase in the expression of genes with antiinflammatory and immunosuppressive characteristics in patients with cHL at diagnosis. Our study also showed that the presence of EBV was related to the expression of proinflammatory cytokines (IL2, IL7 and IL23A). Additionally, treatment reduced sPD1, sPDL1 and IL10 serum levels, that were high at diagnosis. There was a correlation of sPDL1 with presence of B symptoms, advanced staging, presence of bulky disease, increased ESR and decreased albumin, and association of sCTLA4 with highrisk IPS. The treatment had a positive impact on gene expression and on immune checkpoints serum levels with a modification for increased expression of genes that may be related to immune reconstitution. Certainly, more studies investigating the impact of the immune evasion mechanisms of the RS cells and the contribution of the inflammatory microenvironment in the clinical evolution of the patient with cHL will contribute to a better understanding of the characteristic anergy of these patients and to the possible development of new biomarkers and therapeutic strategies.